Tindak Tutur Direktif Dalam Qoutes Akun Instagram @marioteguh - Sari, Citra Purnama; Gunawan, Hafiz; Rustinar, Eli; Hakim, Man (Jurnal Multidisiplin Dehasen (MUDE), 2025)
This research aims to identify and describe the types of directive speech acts used in quotes on the Instagram account @marioteguh during the period of January 1 to February 28, 2025. The method used is qualitative descriptive with content analysis techniques on 57 uploaded quotes. The analysis is conducted using pragmatic theory and the classification of directive speech acts by Ibrahim (1993), which includes commands, invitations, requests, prohibitions, criticisms, and advice. The results of the study show that 84 directive utterances were found with the following distribution: advice (30 utterances), invitations (20 utterances), prohibitions (16 utterances), commands (8 utterances), criticisms (8 utterances), and requests (2 utterances). The dominant type of speech act is advice, reflecting Mario Teguh's motivational language style that emphasizes character building, moral strengthening, and positive encouragement to his followers. Each speech act is interpreted based on context, function, and the purpose Communicative, which generally aims to motivate, provide direction, and shape the positive mindset of the audience. Theoretically, this research enriches the study of pragmatics, particularly in the analysis of directive speech acts on social media. Practically, the results of the research can serve as a reference for learning the Indonesian language, especially in understanding the functions and appropriate use of directive speech acts in communication.